South-Indian horizons : felicitaion volume for Francois Gros on the occasion of his 70th birthday - Gros, Franc̨ois; Chevillard, Jean-Luc; Wilden, Eva; Murugaiyan, A., edt (Publications du Département d'indologie,, 2004)
Zbornik radova, uglavno posvećenih tamilskom jeziku i književnosti